Customer Satisfaction in the Digital Age: Analyzing Private Sector Banks Online Services Quality in Agra (U.P.) - Juhi Rupal; Maria Antony-Raj; Ranveer Singh (AiBi Revista de Investigación, Administración e Ingeniería, 2024)
Banks are crucial players in the operations of financial markets and have a significant impact on maintaining the stability and functionality of a country's economy. In the current highly competitive business landscape, the quality of services plays a vital role in improving consumer satisfaction and fostering customer loyalty. The current study’s aim is to better evaluate the context of customer satisfaction with online banking services and to signify the impact of the same. The present study is also stretched towards finding the determinants that have a high level of influence on customer satisfaction towards online banking services. For the investigation of the work, Agra (Uttar - Pradesh) is considered as the study region, the reason being the mixed population (urban and semi-urban) count in the study region. The study collects data from primary sources using a 5-point Likert scale questionnaire to investigate consumer satisfaction with the attributes of online banking services. By using the purposive sampling method, 400 self-administrated survey questionnaires were distributed to customers of different private banks operating in Agra via social media, from which 250 responses completed the survey. The analysis of the study has shown that the determinants of quality of service have an insightful effect on customer satisfaction with online banking services. In the current study dimensions for service quality -responsiveness, reliability, tangibility, empathy, technological advancement, and customer support were measured. Based on the current state of knowledge for online banking services to provide more insights for the policymakers and decision-making authorities. The banking system always tried to grasp better efforts to understand customer satisfaction.